OPTIMASI SISTEM PERSEDIAAN BAHAN BAKU PT. TC - daniel sembiring; andri andri (LPPM, 2018)
In operation in PT TC has a control system in which the materials available material has significant costs each year so that researchers try to examine that it could not happen. In this study were discussed in detail is the A grade material for class A material has a high percentage is 94.29%. A class of materials is the PAC 8C which is one of the materials used every second and for 24 hours non-stop to produce water. Then the author forecasting material needs in coming years carried out by the method of forecasting the moving average (Moving Average) and results tracking signal is positive, it means the material needs of the coming year are greater than they are today. Tracking signal obtained still included within the limits of ± 4 means that the reliability of forecasting acceptable. Comparison inventory system that has been applied in the company with inventory system models Economic Order Quantity, P, and Min-Max do to make it look which system is better. From the comparison of the three models obtained EOQ method is the inventory control system that is the best because it can save the cost of Rp 162,085,358.Keywords: Economic Order Quantity, System P, Min - Max, ABC Classification